Pemberdayaan Kader Melalui Program “SI KEPO DM” Sebagai Upaya Pencegahan Diabetic Foot Ulcer dengan Pendekatan Paliatif - Muhammad Anis Taslim; Ismonah Ismonah; Linda Pramusinta (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Diabetes mellitus (DM) is a group of chronic metabolic diseases characterized by increased blood glucose levels, which over time can cause serious complications if not treated properly (WHO, 2018). SI KEPO DM (Screening, Recognizing and Caring for Diabetes Mellitus) program is used to prevent and early detect Diabetes Mellitus and the emergence of DM Ulcers. Screening to prevent the emergence of DM ulcers with SMART, namely regular health checks, get rid of cigarette smoke, exercise and physical activity regularly, have a balanced diet, get enough rest and manage stress well. Nowadays, many people do not provide enough fiber in their food, they consume a lot of food that contains cholesterol, saturated fat and sodium, which is made worse by the frequent consumption of foods and drinks that are rich in sugar. Based on a preliminary study, it was found that there was one resident of Karagayu sub-district with a diabetic ulcer who died due to a lack of knowledge regarding the prevention and treatment of Diabetic Ulcer wounds and chose to seek alternative treatment. There is a lack of knowledge regarding screening for early detection of DM as well as how to recognize and care for diabetes mellitus to prevent the appearance of ulcers, so it is necessary to actualize elderly cadres to carry out the Screening, Recognize and Care for Diabetes Mellitus Program as an effort to prevent the appearance of DM Ulcers in the elderly or those who abbreviated as the “SI KEPO DM” program.